Electro-kinetics of conversion of NO3− into NO2−and sensing of nitrate ions via reduction reactions at copper immobilized platinum surface in the neutral medium. (20th June 2020) - Mumtarin, Zannatul; Rahman, Mohammed M.; Marwani, Hadi M.; Hasnat, Mohammad A.
Abstract: The electrocatalytic reduction of NO3 − in neutral medium was investigated at Cuelectro-deposited Pt electrodes. Inherently, the fabricated Pt–Cu electrode surface contains Cu (I) and Cu (II) oxides. The presence of these oxides decreases the efficiency of the electrode pertaining to nitrate reduction reactions (NRR). Since Cu (II) reduction wave and nitrate reduction wave appear closely, this makes complicated for proper kinetic analysis using a Pt–Cu electrode. Thus, oxide deficient electrode was fabricated in–situ by applying a deposition potential at – 0.45 V for 2 min prior to voltammetric scanning for NRR. The voltammetric investigations showed that the oxide deficit (OD) Pt– Cu electrode has an enhanced catalytic effect (i.e. positive shift of the peak potential and an increased reduction current) on NRR than an oxide rich (OR) Pt–Cu electrode. A nitrate ion (NO3 − ) is converted into a nitrite ion (NO2 − ) following a step-wise mechanism, where formal reduction potential and the standard rate constant was evaluated as −0.46 V (vs. Ag/AgCl (sat.KCl) ref. electrode) and 2.48 × 10 −4 cm s −1, respectively. In diagnostic exploration, Differential pulse voltammograms (DPV) were recorded over a large concentration range of NO3 − between 0.12 and 4.75 mM at room temperature, which exhibited linear relationship with two linear dynamic range (LDR) having a break point at 0.99 mM. This electrode displayed an excellent sensitivity (2.3782 μAμM −1 cm −2 ), ultra-low detection limit (LOD: 0.159 μM; S/N = 3), long term stability, very good repeatability and reproducibility. Highlights: Catalytic sites pertaining to NRR are generated while Cu is immobilized on a Pt surface. The surface oxides [Cu(I), Cu(II)] interrupt the NRR process. The copper oxides could be removed in situ by applying a potential of −0.45 V for 2min. The NO3 − to NO2 − conversion occurs via a stepwise mechanism. A Pt–Cu electrode is stable and can efficiently detect nitrate ions from water. Graphical abstract: Image 1